Susceptibility of Spodoptera frugiperda and Chrysodeixis includens (Lepidoptera: Noctuidae) to infections caused by Metarhizium rileyi - Suellen Karina Albertoni Barros; Rafael Major Pitta; Rogério Biaggioni Lopes; Euziclei Gonzaga de Almeida; Fátima Teresinha Rampelotti Ferreira (Pesquisa Agropecuária Tropical, 2020)
Due to the reduced host spectrum of the entomopathogenic fungus Metarhizium rileyi, its pathogenicity against different target insects must be assessed to develop biopesticides capable of controlling more than one pest species. This study aimed to evaluate the susceptibility of the pest species Chrysodeixis includens and Spodoptera frugiperda to different isolates of M. rileyi and, thus, determine a possible influence of the host of origin on the pathogenic activity of these isolates. Three isolates [CG1312 (C. includens as original host), CG381 (S. frugiperda as original host) and a new wild isolate (C. includens as original host)] were tested against larvae of C. includens and S. frugiperda, in third instar age, by treatment of surfaces with conidial suspension, under laboratory conditions. Both species were susceptible to the isolates of M. rileyi, with mortality rates of 53-58 % for C. includens and 74-84 % for S. frugiperda. The results suggest that the host of origin may not be determinant in the selection of pathogenic isolates of M. rileyi against these two pest insects.